2016
DOI: 10.1007/s00277-016-2736-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of high-dose chemotherapy and autologous stem cell transplantation in adolescent and young adults with relapsed or refractory Hodgkin lymphoma

Abstract: High-dose chemotherapy (HDC) and autologous stem cell transplantation (auto-SCT) can salvage many patients with relapsed or refractory Hodgkin's lymphoma (HL). We are reporting the outcome of HDC auto-SCT and the impact of 21 prognostic factors in relapsed and refractory adolescent (14-21 years) and young adult (>21-30 years) (AYA) HL patients. We used Fine and Gray's competing risk analysis method and regression model for outcome analysis. From 1996 to 2013, 290 consecutive patients with biopsy-proven HL unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our data are in line with the clinical characteristics at diagnosis of the AYA population included in Akhtar et al cohort, i.e. high rate of disseminated disease (65 %), of mediastinal involvement (70 %), and of extra-nodal involvement (43 %) [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our data are in line with the clinical characteristics at diagnosis of the AYA population included in Akhtar et al cohort, i.e. high rate of disseminated disease (65 %), of mediastinal involvement (70 %), and of extra-nodal involvement (43 %) [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the median follow-up time 21.5 months and the OS was 70.9%. These data for OS are in the range of previously described data after auto-HSCT [15,16]. Of 184 patients in the study, 21% were colonized by MDRO, particularly by E. coli-ESBL/FQ and VRE, the latter being the only multidrug-resistant gram-positive organism in our cohort.…”
Section: Discussionsupporting
confidence: 83%
“…In a single-institution study of Hodgkin lymphoma, Shafer et al [19] reported an OS of 73% and a progression-free survival of 60% in AYAs treated with autologous HCT. Other studies have highlighted the impact of negative prognostic factors, such as short duration of complete remission, nodular sclerosis pathology, and B symptoms, on outcomes of autologous HCT for Hodgkin lymphoma [20]. A recent CIBMTR study examined long-term outcomes in patients with lymphoma who had survived at least 2 years after undergoing autologous HCT [21].…”
Section: Lymphomamentioning
confidence: 99%